Analisis Numerik Pengaruh Infiltrasi Hujan Terhadap Stabilitas Lereng Di Pangkalan, Sumatera Barat - Rokhmat Hidayat (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2020)
The landslides event was triggered by rain infiltration is an annual occurrence in Indonesia, majority of landslide occur in rainy season. In this research, the case of landslide taken in Pangkalan Area, District of Limapuluh Kota, West Sumatera. The location of the case study is the main access of West Sumatra-Riau, so the landslide in the location is certainly causing close the road. Research phase is geology mapping, geotechnical analysis, and hydrological modeling. Hydrological modeling is done by numerical simulation using laboratory data. The modeling results show that the rain infiltration process resulted in the formation of positive water pressure zone at the foot of the slope, then spread towards the top of the slope. One day after the rainfall, the soil layer had been saturated. The soil layer will saturate the water, so that the slope stability will decrease and the landslide event will occur. To improve the slope stability, it can be done by preventing water from entering the permeable layer with the installation of the shotcrete layer, and draining the water from the slopes by the installation of horizontal drain.